Asas Proporsional dan Asas Itikad Baik dalam Perjanjian Waralaba - Deva, Adam; Rosmidah, Rosmidah (Wajah Hukum, 2023)
The purpose of the study to determine and analyze the urgency of the principle of proportionality and the principle of good faith in the franchise agreement, legal protection and minimization of problems. The problem of how the urgency of the proportional principle and the principle of good faith in the franchise agreement, then the proportional principle and the principle of good faith in the franchise agreement can be a solution in minimizing the problems posed by the franchise agreement and legal protection of the parties.the method used in this study is juridical normative. This research is based on treaty theory, justice theory, proportional principle in Treaty, legal protection. Legal issues the occurrence of ambiguity of norms, that based on Government Regulation No. 42 of 2007 on franchise has contained rules regarding clauses in the agreement clearly as many as 11 clauses that must exist but in the implementation of the standard agreement is an agreement made by one of the parties, causing problems in the future. the results showed that (1) the principle of proportionality and good faith is a unity in a system of checks and balances whose task is to encourage the creation of legal relations in a proportional contract.(2) the principle of good faith and the principle of proportionality in making a franchise agreement, can prevent losses that will be experienced by other parties and is able to minimize the problems that will be caused before the agreement,at the time of the agreement,and after the agreement.